What electronic information resources do physiotherapists prefer to use to support their CPD?. (22nd September 2020) - Clode, Nicholas J.; Darlow, Ben; Rouse, Jack; Perry, Meredith
Abstract: Background and purpose: The way health professionals consume that informal professional education is changing. Physiotherapists are relying more on using electronic sources of information, including social media, to answer clinical questions. This study aims to identify the sources of electronic information physiotherapists in New Zealand use within their informal professional education. Methods: A cross‐sectional survey of 203 physiotherapists and physiotherapy students was undertaken at the National Physiotherapy New Zealand Conference in 2018. Results: One hundred and seventy nine participated in the survey providing a response rate of 88%. Median engagement in electronic professional learning was 1–3 h per week (82/179, 47%). Search engines were the most frequently used resource for accessing professional learning (171/179, 98%). Electronic Journal articles and webinars were seen as the most useful electronic learning resources. Social media sites, such as Twitter and Facebook, were used less frequently. Just over half (94/179, 53%) of participants in the survey reported to regularly critically appraising information. Conclusion: Physiotherapists in New Zealand embark on a significant amount of electronic professional learning. Electronic journal articles are seen as the most valuable resource. Critical appraisal of learning material was not always completed by physiotherapists when consuming informal professional education.